0412 Auditory Awakening Threshold to Evaluate Ability to Awaken after Administration of Lemborexant versus Zolpidem. (27th April 2018) - Murphy, P; Kumar, D; Zammit, G; Rosenberg, R; Moline, M
Abstract: Introduction: Sleep-promoting drugs should facilitate sleep without hindering the ability to awaken to salient stimuli. Here we present baseline results of an ongoing study of the dual orexin receptor antagonist lemborexant on the auditory awakening threshold (AAT) - a measure of environmental responsiveness during sleep. Methods: Double-blind, single-dose, 4-way crossover in healthy females (≥55y) and males (≥65y). Eligible subjects underwent 8hr baseline PSG. After several subjects unexpectedly met the exclusion criterion of latency to persistent sleep (LPS) >30 min, a protocol amendment permitted repeat baseline PSG. Subjects slept with insert earphones. The auditory stimulus apparatus produced 1000Hz tones for 3secs at 15-sec intervals. Starting dB level was 15, increasing 5dB to a maximum 105dB, until the subject stated, "I'm awake." Awakening threshold was the dB level one level below the response. The AAT was initiated 4h after bedtime if subjects were in non-REM stage 2 (N2). If >5 consecutive min of N2 sleep did not occur between 4-4.5h post-bedtime, the AAT was initiated at 4.5h post-bedtime regardless of stage. Results: Of 120 subjects screened, 48 were randomized. Major reasons for failing screening: apnea-hypopnea index >15 (16 subjects) and LPS >30min (19). 9 repeated baseline; 8 subsequently passed the LPS criterion. Of the 48, 5 were awake from the 4-4.5h. Of the 43, 38 (88%) were in N2. The mean intensity required to awaken subjects at baseline was 45dB (range: 15dB - 95dB). 3 (7%) subjects did not awaken to the maximum tone of 105dB; all were in stage N2 at the AAT start. Conclusion: Although healthy, many subjects had prolonged baseline LPS, anecdotally due to anticipatory anxiety associated with the AAT. Allowing for a second baseline appears to mitigate this issue. Due to interindividual variability in baseline AAT, analyses from studies that do not include a time-matched baseline would be potentially problematic. Relatively low dB awakened subjects at baseline, indicating that AAT as implemented may be sensitive to changes in threshold resulting from administration of sleep-promoting drugs. Support (If Any): Eisai, Inc. and Purdue Pharma L.P.